Математическая модель пластинчатого теплообменника для утилизации тепла конденсируемых газовых потоков - Василенко, Александр Анатольевич; Кусаков, Сергей Константинович; Бочарников, Игорь Александрович; Зоренко, Виктор Владимирович; Арсеньева, Ольга Петровна (НТУ "ХПИ", 2018)
В статье представлена математическая модель конденсации пара из смеси с неконденсирующимся газом в каналах пластинчатого теплообменника (ПТО). Модель учитывает изменение параметров процесса вдоль поверхности теплопередачи и локальные особенности процессов тепломассопереноса в каналах ПТО с пластинами различной геометрической формы гофрировки. Она состоит из системы обыкновенных дифференциальных уравнений со значительно нелинейными правыми частями. Разработано программное обеспечение для его решения методом конечных разностей. Адекватность модели подтверждается сравнением с экспериментом по конденсации паровоздушной смеси в модели канала ПТО.

The article presents a mathematical model of steam condensation from a mixture with noncondensable gas in the channels of a plate heat exchanger (PHE). The model takes into account the change in the process parameters along the surface of heat transfer and the local features of the processes of heat and mass transfer in the channels of PHEs with plates of various geometric forms of corrugation. It consists of a system of ordinary differential equations with significantly nonlinear right-hand sides. The entire system of differential equations is given in this paper. In the mathematical model, generalized correlations of the coefficient of friction and heat and mass transfer coefficients are used. The software for its solution by the method of finite differences is developed. The adequacy of the model is confirmed by comparison with the experiment on the condensation of the vapor-air mixture in the model of the PHE channel. Divergences of calculated and measured total thermal loads did not exceed ± 2.8% for all tests performed. The data obtained make it possible to draw a conclusion about the satisfactory accuracy of calculations based on the above model of the total thermal capacity of the PHE.
Mathematical model of plastic heat exchanger for utilization of heat of condensed gas flows
Keywords: интегрированные технологии; теплообменные аппараты; энергосбережение; расчет теплообменников; конденсация газа; пар; integrated technologies; energy saving; heat exchangers calculation; gas condensation